Approximation by the -Szász-Mirakjan Operators - N. I. Mahmudov (Abstract and Applied Analysis)
This paper deals with approximating properties of the q-generalization of the Szász-Mirakjan operators in the case . Quantitative estimates of the convergence in the polynomial-weighted spaces and the Voronovskaja's theorem are given. In particular, it is proved that the rate of approximation by the q-Szász-Mirakjan operators ( ) is of order versus 1/n for the classical Szász-Mirakjan operators.